Oracle database 11g : - Freeman, Robert G. (McGraw-Hill/Oracle Press, 2008)
Realize the full potential of Oracle Database 11g with help from the experts. Written by Robert G. Freeman, and with insightful commentary throughout from Arup Nanda, this Oracle Press guide offers full details on the architectural changes, database administration upgrades, availability and recovery revisions, security enhancements, and programming innovations. Every new and updated feature is covered and presented with screenshots, code samples, tables, and charts. Find out how to take full advantage of all the new and improved capabilities of Oracle Database 11g, including:New Oracle Automatic Storage Management features, such as Fast Disk Resync, Compatibility Attributes, Preferred Mirror Read, and Rolling Upgrade components, Improved Automated Memory Management capabilities,...